(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
This research investigates the analyzing the barriers of Pak-india trade on textile exports by using CGE model. Data were collected from 50 exporters by using simple random technique. Data were analyzed by using SPSS-21 version, A structural questionnaire was developed for the reliability and validity of the data. It was revealed that Exporters opinion on export after decreasing the strength of barriers Exporters have been askedif they are ready toexport moretothe INDIAafter these barriers will beless, and 70% of the exporters said yes, 22% said may be, and 8% said no.Thus,exporter sare positive regarding export to the INDIA. India sex portto the INDIA can be increased if these barriers get less or are removed.It was further revealed that Accordingly, the results suggest that are duction of importtariffs to 10percent wil lincrease Pakistans welfare and terms-of-trade as well. Although one might expect that the reduction of importtariffs would increase the domestic output and there fore increase export sales,this policy reform would adversely affect Pakistan domestic output in most of the sectors because of foreign competition.Asimilar impact can be seen in export sales too